The nightmare before Christmas [videorecording (Blu-Ray)] - Thompson, Caroline, 1956-; McDowell, Michael, 1950-1999; Burton, Tim, 1958- (Disney, 2023)
Bored with the same old scare-and-scream routine, Pumpkin King Jack Skellington longs to spread the joy of Christmas. But his merry mission puts Santa in jeopardy and creates a nightmare for good little boys and girls everywhere!